Atividade ovicida in vitro do extrato salino das folhas do ziziphus joazeiro mart. Em nematoides gastrintestinais de caprinos - Brabosa, Tallyson Nogueira (Universidade Federal Rural do Semi-Árido, 2019)
The goat breeding is an agricultural activity of great economic and social importance. However, parasitism by gastrointestinal nematodes causes large production losses associated with the development of parasitic chemical resistance. As this resistance has worsened over the years, the search for alternative methods has become essential for productive activity. The objective of this study was to analyze phytochemically the saline extract obtained from the leaves of Ziziphus joazeiro Mart., To evaluate its ovicidal activity against gastrointestinal parasites of goats (IGN) and its acute toxicity against nauplii of Artemia salina. For this, Z. joazeiro leaves were collected, dried at room temperature and processed to prepare the salt extract. Once the extract was obtained the phytochemical analysis was performed. For the in vitro hatchability test, IGN parasite eggs were recovered from fecal samples collected in naturally infected goats and incubated in addition to the different concentrations of the extract. An assay to evaluate the toxicity of Z. joazeiro saline extract was performed against Artemia salina nauplii. As a result, the phytochemical components were identified: saponins, tannins, flavonoids and alkaloids. The Z. joazeiro leaf extract presented satisfactory inhibition results of 99.53%, 75.28% and 67.66% at the concentrations of 20.288mg / ml, 10.144mg / ml and 5.072mg / ml respectively. The extract showed a LC50 of 10.14 mg / ml in the toxicity test. These data show that crude salt extract of Z. joazeiro presented substances considered bioactive, with antiparasitic effects under eggs of gastrointestinal parasites of goats
Keywords: Caprino; Parasito; Fitoterápico; Antiparasitário; Goat; Parasitic; Phytotherapeutic; Antiparasitic; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE